Co-occurrence and estimation of the risk of total aflatoxins (B1, B2, G1, and G2) and ochratoxin A in agri-food products consumed in Chile. (April 2023) - Calderón, R.; Palma, P.; Godoy, M.; Vidal, M.; Rivera, A.
Abstract: The consumption of agri-foods contaminated with mycotoxins poses a serious threat to human health. In this study, we evaluated the presence of total aflatoxins (AFs) and ochratoxin A (OTA) in various agri-food products of national and imported origin in Chile that are consumed daily. A total of 653 samples of cocoa (22), oats (50), ginger (62), pepper (131), coffee (42), raisins (34), turmeric (60), nutmeg (30), cereals (60), flour (47), walnuts (16), dried fruits (18), pistachios (10), hazelnuts (7), almonds (20), peanuts (35), and tea (9) were collected from 2018 to 2020 in markets and supermarkets in Chile by the Mycotoxin Monitoring Program of the Ministry of Health of Chile. Contamination by AFs occurred mainly in nutmeg, pepper, and ginger in 2018, as these compounds were not detected in 2020. The detection frequency for OTA was higher than that of the AFs, and it was mainly present in turmeric, ginger, and pepper. The Estimated Daily Intake (EDI) in nutmeg for AFs and OTA does not exceed the tolerable weekly or daily intake levels proposed by international bodies.